ASSOCIATION BETWEEN SERUM URIC ACID AND METABOLIC SYNDROME - Js, Thaslima Nandhini; G, Savitha Basker; V, Vishnupriya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Metabolic syndrome is a cluster of disease condition characterized by truncal obesity, hypertriglyceridemia, elevated blood pressure, and insulin resistance. An excessive circulating uric acid (UA) level even within normal range is always comorbid with metabolic syndrome and its components. The aim of the current study was to investigate the association between metabolic syndrome and serum UA level. Methods: A total of 60 subjects were divided into two groups of healthy (30 individuals) and metabolic syndrome patients (30 individuals) from dental outpatient department of Saveetha Dental College and Hospitals. 5 ml of fasting venous blood was collected in the plain collection tubes and centrifuged, and then serum was separated. Then, the serum was used to analyze the fasting blood glucose, serum triglycerides (TGLs), and serum UA by GOD-POD, enzymatic colorimetric, and uricase method, respectively. A statistical analysis was performed using Student's t-test. p<0.05 was considered to be statistically significant. Result: Mean body mass index (BMI), fasting blood sugar (FBS), TGL, and UA level of control group were 23.36±1.81, 84.45±13.1, 110.9±22.6, and 3.48±1.21 respectively. Mean BMI, FBS, TGL, and UA level of study group were 35.24±3.04, 122.85±23.3, 212.1±39.6 and 9.08±2.63 respectively. There is a significant difference between these two groups with p<0.0001. Conclusion: This study showed that those individuals with metabolic syndrome have higher UA level that indicates hyperuricemia which is a significant predictor of metabolic syndrome.